2018
DOI: 10.1128/aac.00395-18
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Radiological, and Microbiological Characteristics of Mycobacterium simiae Infection in 97 Patients

Abstract: is a rare species of slow-growing nontuberculous mycobacteria (NTM). From 2002 to 2017, we conducted a retrospective study that included all patients with NTM-positive respiratory samples detected in two university hospitals of the French overseas department of Reunion Island. We recorded the prevalence of in this cohort, as well as the clinical, radiological, and microbiological features of patients with at least 1 sample positive for In our cohort, 97 patients (15.1%) were positive for Twenty-one patients (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 22 publications
5
11
2
Order By: Relevance
“…In our study and among M. simiae, only two of the 11 tested antimicrobial agents were associated with high susceptibility: clarithromycin (96%) and amikacin (93%) while the remaining tested agents revealed high resistance (70%-100%). Compared to studies from other countries, the 96% susceptibility to clarithromycin in our study was close to that reported from USA (91%) [24] and Réunion Island (100%) [25], while other countries reported very low susceptibility i.e. Iran (0%) [26], UK (19%) [27], and Netherlands (25%) [28].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In our study and among M. simiae, only two of the 11 tested antimicrobial agents were associated with high susceptibility: clarithromycin (96%) and amikacin (93%) while the remaining tested agents revealed high resistance (70%-100%). Compared to studies from other countries, the 96% susceptibility to clarithromycin in our study was close to that reported from USA (91%) [24] and Réunion Island (100%) [25], while other countries reported very low susceptibility i.e. Iran (0%) [26], UK (19%) [27], and Netherlands (25%) [28].…”
Section: Discussionsupporting
confidence: 80%
“…For Amikacin, the 93% susceptibility rate found in our isolates was comparable to that from Iran (86%) [26], UK (89%) [27] and Réunion Island (87%) [25] but higher than that reported from USA (14%) [24] and Netherlands (0%) [28]. A relatively high susceptibility to other antimicrobial agents was reported for rifabutin (88%) from Iran [26] and for ciprofloxacin from UK [27] and Réunion Island [25] (64% and 87%, respectively).…”
Section: Discussionsupporting
confidence: 76%
“…In recent years, clinical isolation of M. simiae has been widely reported from different regions of the world such as Europe, the United States and the Middle East [7] , [30] , [31] , [32] , [33] , [34] , [35] . M. simiae was also reported to be the most common NTM species in India (22%), France (15.1%), Oman (14.3%), United States (3.0%) and Saudi Arabia (1.4%) [1] , [36] , [37] . Uses of newest laboratory diagnostic methods were assumed to be one of the reasons for increased reports of this organism.…”
Section: Discussionmentioning
confidence: 99%
“…simiae was initially considered as an environmental pathogen and is rarely associated with human illness [4]. More recently, M. simiae has been described to cause a spectrum of clinical syndromes, ranging from an asymptomatic infection to a fatal disseminated disease [5,18,19].…”
Section: What Is the Clinical Spectrum Of M Simiae Infections?mentioning
confidence: 99%
“…Treatment can be deferred in cases where M. simiae isolation is asymptomatic, as demonstrated in a study from Israel by Lavy and colleagues, in which M. simiae was isolated only once in more than 80% of asymptomatic patients that did not require treatment [14]. In a cohort of 97 patients with positive M. simiae cultures in the French Réunion Island, only 8% required treatment [18]. However, a recent cohort study from Lebanon [4], which reported a prevalence of M. simiae among NTM that was more than twice that of Réunion Island, reported a higher pathogenicity (47% versus 21.6% respectively) [24], suggesting a possible underestimation of the virulence of the organism.…”
Section: Is It Always Alarming To Isolate M Simiae From a Culture Spmentioning
confidence: 99%